2006
DOI: 10.1038/nature05404
|View full text |Cite
|
Sign up to set email alerts
|

Pheromonal communication in vertebrates

Abstract: Recent insights have revolutionized our understanding of the importance of chemical signals in influencing vertebrate behaviour. Previously unknown families of pheromonal signals have been identified that are expanding the traditional definition of a pheromone. Although previously regarded as functioning independently, the main olfactory and vomeronasal systems have been found to have considerable overlap in terms of the chemosignals they detect and the effects that they mediate. Studies using gene-targeted mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
350
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 438 publications
(364 citation statements)
references
References 100 publications
5
350
2
7
Order By: Relevance
“…In the case of pregnancy block (Bruce effect) the pregnancy of recently mated females is disrupted if these females are exposed to the urine of an unfamiliar male [12,15,18]. This effect is based on females' learning of the mating male's olfactory signature during the immediate post-copulatory period.…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of pregnancy block (Bruce effect) the pregnancy of recently mated females is disrupted if these females are exposed to the urine of an unfamiliar male [12,15,18]. This effect is based on females' learning of the mating male's olfactory signature during the immediate post-copulatory period.…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
“…For example, the volatile urinary compound (methylthio) methanethiol (MTMT) has been shown to activate a subset of mitral cells in the MOB, and when added to urine, enhances urine attractiveness to female mice [62]. In this context, the anatomical segregation of the two systems and the extensive functional differences between them have given rise to the traditional view that the MOE detects volatile odorants in the environment while the VNO detects non-volatile pheromones [15,19]. In support of this functional dichotomy, Luo et al have demonstrated using electrophysiological recordings of mitral cells in the AOB in behaving animals that these cells are only activated when mice make direct physical contact with the odorant source (either the face or anogential regions of an anaesthetised stimulus female [66]).…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The mouse genome encodes for $ 38 MUPs 5,6 which have been classified into four groups based on nucleotide sequence similarity and tissuespecific expression patterns. Group 1 MUPs are expressed mainly in the liver and kidney and excreted into the urine at high levels.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, pheromones are detected both by the main olfactory bulb and the vomeronasal organ (VNO). 1,19 It has been proposed that the nasal MUP isoforms may function in facilitated transport to olfactory and vomeronasal receptors. 20 MUP isoform IV (MUP-IV), belongs to group 4 9 and is the only MUP known to be expressed in the VNO.…”
Section: Introductionmentioning
confidence: 99%